Outcomes of a new slowly resorbable biosynthetic mesh (Phasix™) in potentially contaminated incisional hernias: A prospective, multi-center, single-arm trial. (November 2020) - van Rooijen, Mathilde MJ.; Jairam, An P.; Tollens, Tim; Jørgensen, Lars N.; de Vries Reilingh, Tammo S.; Piessen, Guillaume; Köckerling, Ferdinand; Miserez, Marc; Windsor, Alastair CJ.; Berrevoet, Frederik; Fortelny, René H.; Dousset, Bertrand; et al.
Abstract: Background: Resorbable biomaterials have been developed to reduce the amount of foreign material remaining in the body after hernia repair over the long-term. However, on the short-term, these resorbable materials should render acceptable results with regard to complications, infections, and reoperations to be considered for repair. Additionally, the rate of resorption should not be any faster than collagen deposition and maturation; leading to early hernia recurrence. Therefore, the objective of this study was to collect data on the short-term performance of a new resorbable biosynthetic mesh (Phasix™) in patients requiring Ventral Hernia Working Group (VHWG) Grade 3 midline incisional hernia repair. Materials and methods: A prospective, multi-center, single-arm trial was conducted at surgical departments in 15 hospitals across Europe. Patients aged ≥18, scheduled to undergo elective Ventral Hernia Working Group Grade 3 hernia repair of a hernia larger than 10 cm 2 were included. Hernia repair was performed with Phasix™ Mesh in sublay position when achievable. The primary outcome was the rate of surgical site occurrence (SSO), including infections, that required intervention until 3 months after repair. Results: In total, 84 patients were treated with Phasix™ Mesh. Twenty-two patients (26.2%) developed 32 surgical site occurrences. These included 11 surgical site infections, 9 wound dehiscences, 7 seromas, 2 hematomas, 2 skin necroses, and 1 fistula. No significant differences in surgical site occurrence development were found between groups repaired with or without component separation technique, and between clean-contaminated or contaminated wound sites. At three months, there were no hernia recurrences. Conclusion: Phasix™ Mesh demonstrated acceptable postoperative surgical site occurrence rates in patients with a Ventral Hernia Working Group Grade 3 hernia. Longer follow-up is needed to evaluate the recurrence rate and the effects on quality of life. This study is ongoing through 24 months of follow-up. Highlights: Biosynthetic mesh is relatively new and showed (pre-clinically) favourable properties. Biosynthetic mesh showed an acceptable complication and infection rate in potentially contaminated hernias. Despite resorption, biosynthetic mesh did not lead to early hernia recurrences.